2002
DOI: 10.1108/10610420210419522
|View full text |Cite
|
Sign up to set email alerts
|

An examination on multiple celebrity endorsers in advertising

Abstract: Celebrity endorsement advertising is a prevailing advertising technique. Some marketers choose to utilize multiple celebrities to promote their products or brands. Nevertheless, it is surprising that so little research has focused on this phenomenon. This research discussed advantages and potential concerns of multi-celebrity endorsement advertising and documented the actual use of multiple celebrity endorsers in the milk mustache campaign in the USA. We analyzed the content of the 50 milk mustache ads appeari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
4
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 13 publications
1
100
4
5
Order By: Relevance
“…According to Khatri (2006) celebrity endorsement is the utilization of the celebrity's names in the product or services advertisements, where celebrities may or may not be the experts. Though, the authors such as Boorstin (1961), McCracken (1989) and Khatri (2006) define celebrity endorsement, this study uses the McCracken (1989) definition, where this definition is adopted by many recent celebrity endorsement related studies (e.g., Hsu & McDonald, 2002;Banyte, Stonkiene, & Piligrimiene, 2011;Doss, 2011;Fleck, Korchia, & Le Roy, 2012;De Los Salmones, Dominguez, & Herrero, 2013). Ohanian (1990) indicates celebrity endorsement dimensions are: (a) trustworthiness, (b) expertise and (c) attractiveness.…”
Section: Definitions Of Celebrity Endorsementmentioning
confidence: 99%
“…According to Khatri (2006) celebrity endorsement is the utilization of the celebrity's names in the product or services advertisements, where celebrities may or may not be the experts. Though, the authors such as Boorstin (1961), McCracken (1989) and Khatri (2006) define celebrity endorsement, this study uses the McCracken (1989) definition, where this definition is adopted by many recent celebrity endorsement related studies (e.g., Hsu & McDonald, 2002;Banyte, Stonkiene, & Piligrimiene, 2011;Doss, 2011;Fleck, Korchia, & Le Roy, 2012;De Los Salmones, Dominguez, & Herrero, 2013). Ohanian (1990) indicates celebrity endorsement dimensions are: (a) trustworthiness, (b) expertise and (c) attractiveness.…”
Section: Definitions Of Celebrity Endorsementmentioning
confidence: 99%
“…Endorsement advertising also enhances the product recognition (Maclnnis, Rao & Weiss (2002), Laffery & Goldsmith (1999), Goldsmith, Lafferty & Newell 2000). In recent years celebrity advertisement increase tremendously and many companies are adopting this strategy (Hsu & McDonald, 2002). According to the research of an advertising magazine it is concluded that US is spending billion of US dollar for TV commercial advertising and about 10% of US dollar are paid to wellknown stars (celebrities).…”
Section: Consumer Purchase Intentionsmentioning
confidence: 99%
“…Aunque la mayoría de trabajos han utilizado técnicas experimentales para demostrar la eficacia de personalidades, el análisis de contenido se considera la técnica adecuada para analizar la forma y presencia de portavoces en publicidad (Belch & Belch, 2013;Black & Choi, 2013;Choi, Lee & Kim, 2005;Hsu & McDonald, 2002;Stout & Moon, 1990). Asimismo, los estudios precedentes se han centrado en televisión y medios gráficos --especialmente revistas--, no habiendo encontrado ningún trabajo específico que analice la figura del portavoz en la publicidad radiofónica.…”
Section: Marco Teórico Y Preguntas De Investigación 21 El Uso De Pounclassified